Body percussion and selective attention. Interdisciplinary quantitative study through neuromotricity activities BAPNE method based on the dual task in Primary Education - Francisco Javier Romero Naranjo; Francisco Javier Pujalte Cantó; Antonio Francisco Arnau-Mollá (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this research was to test whether the neuromotricity activities of the BAPNE method based on the dual task could improve selective attention and concentration in 5th grade primary school pupils. A quantitative approach was used, with a quasi-experimental design between subjects and with repeated measures before and after the intervention (pretest-intervention-posttest). The research was carried out in two schools in Alicante (Spain). The sample consisted of N=114 students between 10 and 11 years of age with similar socio-economic and cultural characteristics. A non-probabilistic convenience sampling was used, dividing the sample into an experimental group (n=66) and a control group (n=48). The Spanish adaptation of the d2 attention test was used as the assessment instrument. Statistical data were processed using SPSS, JASP and Excel. Statistical decision-making was based on a significance level of alpha=0.05. Samples were tested for normality, parametric and non-parametric tests were applied, and effect sizes were calculated. The main results of the intra-subjects analysis were statistically significant in favour of the experimental group in the variables TRPOST (p=<.001), DifTR (p=<. 001), TAPOST (p=.025), DifTA (p=.021), CPOST (p=<.001), DifC (p=.021), VARPOST (p=<.001), DifVAR (p=.002), TR+POST (p=<.001), and DifTR+ (p=<.001). Three variables that showed differences in the pretest were invalidated. The within-subjects analysis was also favourable for the experimental group. In conclusion, an affirmative answer to the purpose of this research is presented.